Solid-State 13C CP MAS NMR Spectroscopy as a Tool for Detection of (1→3, 1→6)-β-D-Glucan in Products Prepared from Pleurotus ostreatus. (31st July 2013) - Fričová, O.; Koval'aková, M.
Abstract : The 13 C CP/MAS NMR solid-state NMR technique was used to detect the presence of β -D-glucan and trace compounds in samples prepared from dried, naturally grown oyster mushroom ( Pleurotus ostreatus ) and commercially available products of dried, specially cultivated oyster mushroom and β -D-glucan isolated from this mushroom. The NMR spectra of all samples displayed signals typical for (1→3, 1→6)- β -D-glucan; however, signals which could be assigned to other trace compounds—(1→3)- α -glucan, chitin, and proteins—were also observed in the spectra. The amount of trace compounds was negligible in the commercially available products.